PENGAMATAN CAHAYA MATAHARI UNTUK MENENTUKAN JARI-JARI BUMI: SUBUAH EKSPERIMEN PADA MATAKULIAH FISIKA KEBUMIAN LANJUT - Nur Islami (Jurnal Pendidikan, 2019)
In Advanced Earth Physics courses, one of the topics discussed is the characteristics of the earth. One of the topic deals with how to measure the radius of the earth. The purpose of this study is to provide an experiment for students so they can understand how to measure the radius of the earth. A simple but accurate method for measuring the radius of the Earth using a video camera is explained in this study. A demonstration is given to students. Then students were requaired to make their own observations and calculate the radius of the earth obtained from each experiment. The results of student experiments show that the radius of the earth is 6243.94 km with a standard deviation of 14.70 km. The average results of these 35 students are within 1.9% of the average value of the earth's radius which is currently accepted at 6371 km. This experiment is very useful in giving students a good understanding so they understand how to determine the radius of the earth.